Advancing Digital Extension Education: Development and Validation of Digital Learning Engagement Scale (Indian Journal of Extension Education, 2025)
Digital transformation has revolutionized extension education and professional upskilling, revealing significant gaps in learning engagement assessment within digital contexts. Conventional classroom-based scales fail to capture multifaceted digital engagement in AI-augmented, asynchronous environments, overlooking self-regulation difficulties, learner isolation, and adaptive interactions. This hampers organizations and extension practitioners from identifying disengagement early and designing evidence-based interventions. Addressing this, an 18-item Digital Learning Engagement Scale (DLES) was developed through robust psychometric evaluation, content validation by eight experts. Data was collected from 461 digital learning platform users. Exploratory factor analysis (n=227) using principal axis factoring is chosen to handle correlated engagement dimensions, identified a stable four-factor structure (behavioural, emotional, cognitive and psychological engagement) explaining 66.93 per cent of variance (KMO=0.937, Bartlett’s p < 0.001). Confirmatory factor analysis confirmed excellent model fit (χ²//df = 1.34, CFI = 0.945, TLI = 0.935, RMSEA = 0.065, SRMR = 0.057) with strong internal consistency (α = 0.86 -0.91), composite reliability (CR = 0.87- 0.91), convergent and discriminant validity. The DLES enables extension professionals, educators, and organizations to assess engagement, identify barriers, and implement targeted data-driven interventions, improving retention and learning effectiveness.